Availability and functioning of neonatal care units and neonatal mortality across five regions in Tanzania: a baseline cross-sectional study in 127 CEmONC health facilities - Hege Ersdal; Nahya Salim; Siren Rettedal; Castory Munishi; Robert Moshiro; Felix Ambrose Bundala; Benjamin A Kamala; Godfrey Guga; Habib R Ismail; Paschal Francis Mdoe (BMJ Global Health)
Background The neonatal mortality rate in Tanzania has remained persistently high, at 24 deaths per 1000 live births. To halve the current death rate by 2030, the WHO recommends that by 2025, at least 80% of districts should have a neonatal care unit (NCU) and use a continuous positive airway pressure (CPAP) device for respiratory support, among small and sick newborns. This study describes the availability and functioning of NCUs and facility-based neonatal mortality in Tanzania.Methods From December 2020 to March 2021, a cross-sectional study was conducted in 127 health facilities in five regions. Data were collected using structured checklists. The presence of a neonatal intensive care unit or a high dependency unit, a kangaroo mother care ward and a general neonatal ward defined a minimum national NCU recommendation. The presence of one or more admission beds and a neonatal CPAP in the established NCU described the functioning.Results Of all health facilities providing comprehensive emergency obstetric and newborn care services, 48% (61/127) had established an NCU. Only 3% (4/127) met the minimum national NCU recommendation. NCUs were significantly less available in health centres and district hospitals than in regional referral hospitals (p<0.001), and less in public and private facilities than in faith-based organisations (p = 0.001). Moreover, only 31% (40/127) of facilities had at least one neonatal admission bed, and 3% (4/127) had a neonatal CPAP in the NCU. Besides, 75% (30/40) of the functioning NCUs, had one to four beds only. Only 17% (22/127) of facilities had a neonatal admission register. Neonatal admissions and deaths were significantly lower in facilities without functioning NCUs and admission registers (p<0.008, 0.001, respectively). The early (0–7 days) neonatal mortality accounted for 96% (529/550) of registered neonatal deaths.Conclusions Health facilities with functioning NCUs are scarce, with few admission beds and CPAP devices. The lack of admission registers implies a significant under-reporting. Tanzania needs to improve the availability of functioning NCUs, with adequate admission beds and equipment to end preventable neonatal deaths, as per global targets, by 2030